SPECIAL AND MILITARY PURPOSE PRODUCTS: SHAPE-FORMING AND CONSTRUCTIVE FEATURES - Остапенко, Н. В.; Мамченко, Я. О. (Art and Design, 2023)
The aim of the work is the analysis of the range of products for special and military purposes and the systematization of modern varieties according to various characteristics. And also improvement of the information base of constituent elements for their rational selection and expanding the range of modern products. Methodology. The study of military and special-purpose products’ compositional and constructive solutions is based on a comprehensive approach and general scientific research methods. The methods of system-structural analysis, comparison, analysis and synthesis, generalization, and typological analysis were used when grouping the elements of products. It was established that the components of modern sewing products are structural and compositional elements, which do not include nodes, details, or joints, which are conventionally divided into basic and additional; elements fixing the position of parts of the product relative to the human body; elements of adaptation to morphological features of the consumer. The most popular varieties of products in the set were singled out, their compositional and constructive-technological structure were analyzed, and an information base of elements was developed, in particular, it is a graphic part of the visual variability of the product set according to the specifics of professional and qualification activities. It is proven that the effectiveness of the product largely depends on the rational combination of its constituent elements, their mutual location, and the consistency of parameters.It was determined that the selection of criteria, namely the size, configuration, location, method of connection, etc., of the elements of the product is carried out following the operating conditions, features of professional activity and performed tasks, requirements for products, etc. Scientific novelty. Various types of components of modern military and special purpose products are systematized according to different classification groups and their functional and constructive features are described, and placement options and compositional organization are proposed. Practical significance. The research results contribute to the expansion of knowledge on the design of ergonomic products for military personnel and workers, for the further implementation of the components of the information base in the development of new highly effective modern products with predictable characteristics.